Lifetime of Plasma Etched Copper Lines. (30th April 2019) - Su, Jia Quan; Li, Mingqian; Kuo, Yue
Abstract : The electromigration failure process of the plasma etched Cu line has been studied. The surface color changed due to joule heating that caused surface oxidation for the case of the uncapped copper line or the diffusion of copper into the TiW capping layer for the case of the capped copper line. The line temperature was estimated based on the assumption of the negligible heat loss to the glass substrate. The resistance of the copper line also changed with the stress time. Therefore, the copper line failure process can be predicted from the observation of changes of the surface color and line resistance.